2021
DOI: 10.2174/1871526520666200128162646
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Morganella Morganii and Providencia Species from Clinical Samples in a Tertiary Care Hospital in North India

Abstract: Introduction: The members of the tribe Proteeae, Morganella and Providencia are being increasingly recognized as important pathogens. The spectrum of disease caused by them is wide and in reported cases the mortality is high. Previously both these pathogens were considered to be rare pathogens as the potential to cause nosocomial transmission and infection was not much studied. But their phenomenal evolution and increase in multidrug-resistance (MDR) strains of these pathogens are posing a major threat toward … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Acintobactoer spp is presented strongly in the results as a causative agents pus-causing microbes which is formed approximate 3.1% of pus's infections in Jordan, 2% for MDR strains and 1% for non MDR species, the risk in Acintobactoer spp infections in its membership among ESKAPE group (Enterococcus faecium, Staphylococcus aureus, Klebsiella pneumoniae, Acinetobacter baumannii, Pseudomonas aeruginosa, Enterobacter cloacae) and the resistancey and spreading within healthcare centers [13,14]. E. coli caused approximate 1/5 over all of the pus's infections by percentage of 21.4%,this showed that the most pus-causing infections caused by E. coli non extended spectrum βlactamase (ESβL), but the percentage of the Nonhemolytic streptococci bacteria was relatively high by percentage of 9.2%, and Streptococcus agalactiae ( group B) formed 4.1%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acintobactoer spp is presented strongly in the results as a causative agents pus-causing microbes which is formed approximate 3.1% of pus's infections in Jordan, 2% for MDR strains and 1% for non MDR species, the risk in Acintobactoer spp infections in its membership among ESKAPE group (Enterococcus faecium, Staphylococcus aureus, Klebsiella pneumoniae, Acinetobacter baumannii, Pseudomonas aeruginosa, Enterobacter cloacae) and the resistancey and spreading within healthcare centers [13,14]. E. coli caused approximate 1/5 over all of the pus's infections by percentage of 21.4%,this showed that the most pus-causing infections caused by E. coli non extended spectrum βlactamase (ESβL), but the percentage of the Nonhemolytic streptococci bacteria was relatively high by percentage of 9.2%, and Streptococcus agalactiae ( group B) formed 4.1%.…”
Section: Discussionmentioning
confidence: 99%
“…The multidrug resistant (MDR) and pan drugresistant (PD) gram-negative bacteria, is less prevalent than MRSA. Recently, the MDR and extensively drug resistant (XDR) strains of Mycobacterium tuberculosis were starting to make an actual threat in the developing world [9,11,[12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, Providencia spp. has been reported as a normal flora of the human intestinal tract and are the most common causes of infections in hospitalized patients [26,27]. However, some Providencia species were isolated from wastewater and contaminated soil [28,29].…”
Section: Isolation and Identification Of The Marinementioning
confidence: 99%